STIGMATIZATION, LABOR EXPLOITATION AND PATRIARCHALISM IN VENEZUELAN IMMIGRATION IN PERU - LOAYZA JAVIER, Jerjes (2021)
Venezuelan migration has forced many of its inhabitants to become refugees who appealed to an unusual mass migration to different countries in the region. This represented, to this day, the most shocking migratory event in Peru, living with a different culture and dynamic of life. The clash between Peruvians and Venezuelans would include possible xenophobic logic that would radicalize inequality. The article proposes to understand the intersubjective scope developed in the body and sensitivities in Venezuelan migrants in the interval that goes from 2017 to 2019. The methodology addresses biographical methods such as interviews and the life history of Venezuelan immigrants. Prejudices and xenophobic evaluations are identified between a population of one nationality and another that is difficult to overcome given the discriminatory exercise that the Peruvian population applies to the Venezuelan population. This, in turn, survives all kinds of negative distinctions by appealing to a social capital that elevates their nationality and their fellow citizens as the answer to the problems they experience every day in search of a basic livelihood.